Effects of 11β-hydroxysteroid dehydrogenase type 1 enzyme in the liver in fructose induced metabolic syndrome rat model - Norshalizah M,; Zar, Chi T; Farihah Suhaimi, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Excessive expression and activity of 11β-hydroxysteroid dehydrogenase enzyme type 1 (11β-HSD1) enzyme in mature adipocyte leads to obesity and metabolic syndrome. Fructose in drinking water was proven to induce metabolic syndrome in male Wistar rat. Hence, the aim of the study was to assess the effects of expression and activity of 11β-HSD1 enzyme in the liver in an established metabolic syndrome rat model induced by fructose drinking water. Twelve male Wistar rats were randomly divided into two groups: Control group, C (n=6) and Fructose drinking water 20%, F20 (n=6). The food and fluid intake were given as ad libitum for eight weeks. At the end of the experiment, the expression of 11β-HSD1 enzyme in the liver was measured by immunohistochemical staining method. The score was given according to the intensity of the staining of the granules in the hepatocyte cytoplasm which was measured using double-blinded method. Meanwhile, the activity of 11β-HSD1 enzyme in the liver was measured using ELISA technique. Following eight weeks of consumption of fructose drinking water, the F20 group showed an increased in both expression and activity of 11β-HSD1 in the liver. The obtained data clearly suggest that 11β-HSD1 enzymes in the liver may play a role in the development of metabolic syndrome and its complications in male Wistar rat.